O uso da somatotropina bovina recombinante em reprodução bovina - Bragaglia, Gabrielle Nellis [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The recombinant bovine somatotropin (rbST) at first, had its widespread use in dairy cows in order to increase milk production. Currently, it has been studied frequently and use their influence both in bovine milk, such as cutting. Its production has been an evolution to the science, using bacteria to produce recombinant DNA. Most authors that have studied and obtained positive results, such as increasing the number of ovarian follicles larger than five millimeters, among others. Its action takes place directly on the ovary, follicles, corpus luteum, the granulosa cells, oviduct, myometrium, endometrium and placenta, where they were found receptors, or indirectly through the release of insuline like growth factor-1 (IGF-1). Therefore, the objective of this work is to explain the importance of bST in bovine as well as the usefulness of this, its mechanism of action and the benefits it can bring when combined with other biotechnology, such as superovulation, embryo transfer, synchronization of estrus, and others

A somatotropina bovina recombinante (rbST) teve seu uso disseminado, primeiramente, em vacas leiteiras com o intuito de aumentar a produção de leite. Atualmente, tem sido estudado com freqüência seu uso e influência na reprodução de bovinos tanto de leite, como de corte. A sua produção foi uma evolução para a ciência, sendo utilizadas bactérias para a produção do DNA recombinante. A maior parte dos autores que a estudaram, obtiveram resultados positivos, como por exemplo, o aumento do número de folículos ovarianos maiores que cinco milímetros, entre outros. Sua ação se dá diretamente no ovário, folículos, corpo lúteo, células da granulosa, oviduto, miométrio, endométrio e placenta, onde foram encontrados receptores; ou indiretamente através da liberação do fator de crescimento semelhante à insulina-1 (IGF-1). Portanto, o objetivo desse trabalho é expor a importância da bST na reprodução de bovinos, bem como a utilidade desta, seu mecanismo de ação e os benefícios que esta pode trazer quando associada a outras biotécnicas, como por exemplo, superovulação, transferência de embriões, sincronização de cio, entre outras
Keywords: Reprodução animal - Bovino; Bovine